Comparative genome integrity of riverine buffalos (Bubalus bubalis) under tropical climatic conditions - Kumar, Anil (Indian Journal of Dairy Science, 2014)
The purpose of the present study was to evaluate the genome integrity of indigenous buffalo breeds- Murrah and Nilli-Ravi (same age, sex and environmental conditions) in the northern states Punjab (Patiala) and Haryana (Hisar & Karnal) of India. The climographs based on the monthly mean temperature (30 years) and monthly mean relative humidity of Hisar, Karnal and Patiala regions were prepared for assessment of climatic conditions of particular regions in which animals were reared throughout the year. Seventy five buffaloes of the two breeds were used in this study. All animals were kept in organized herd at three different farm locations. Comparative cytogenetic analysis was made between the two breeds of buffalo. The cytogenetic studies of peripheral lymphocytes included chromosomal aberrations (CAs) and sister chromatid exchange (SCE). The mean number of gaps in Murrah buffalo of Karnal and Hisar regions were 12.48±4.12 and 10.86±3.65 respectively. Similarly, the mean number of gaps in Nilli-Ravi breed of buffalo from Patiala was 7.0±2.27. The mean frequency of chromosomal breaks in Murrah buffalo from Hisar and Karnal were 5.96±1.92 and 5.44±2.72 and 3.1±1.97 in Nilli-Ravi respectively, the difference was statistically significant. The frequency (mean±SD) of sister chromatid exchanges/per cell in Murrah buffaloes from Hisar and Karnal were 6.64±2.21 and 6.26±1.92 and for Nilli-Ravi was 3.52±1.87. The results of cytogenetic analysis between the two buffalo breeds reared under same climatic conditions at different farm locations (Haryana and Punjab) reveal significant (P ≤ 0.01) differences in their genome integrity as detected by CAs and SCEs.